Determinants of an effective antibiotic campaign: Lessons from Hong Kong. Issue 4 (December 2014) - Ho, Mei Lin; Cowling, Benjamin John; Seto, Wing Hong; Wong, Lai Chin; Wong, Tin Yau
Abstract: Hong Kong launched a publicity campaign on the use of antibiotics and antibiotic resistance in March/April 2011. Two population surveys were conducted in November 2010 ( N  = 1569; response rate 69.2%) and June 2011 ( N  = 1527; response rate 66.6%) before and after the campaign, respectively, to evaluate its impact. Adults aged ≥18 years were asked about their knowledge and attitude related to antibiotic use and antibiotic resistance. Information obtained from health professionals had the highest mean impact score. There was a significant increase in the proportion of respondents knowing that antibiotics could not cure influenza (from 58.0 to 65.0%; P  < 0.001) or viral infections (from 24.9 to 29.0%; P  = 0.002). Over one-quarter (27.7%) of respondents could recall the campaign, mostly through announcement of public interest (API) on television/radio. After regression analysis, age, personal hygiene practices in daily life, and the attitude that everyone had a role to play in alleviating the problem of antimicrobial resistance were found to be associated with campaign awareness.